Alan Seeger: medievalism as an alternative ideology - Dayton, Tim (My University, 2012)
The American poet Alan Seeger imagined the First World War as an opportunity to realize medieval values, which were embodied for him in Sir Philip Sidney. Sidney epitomized Seeger’s three ideals: “Love and Arms and Song,” which contrasted with the materialism and sophistication of modernity. His embrace of “Arms” and the desire for intense, authentic experience led Seeger, who was living in Paris in August 1914, to enlist in the French Foreign Legion, in which he served until his death in combat in July 1916. As an infantryman Seeger had extensive experience of the Western front. This concrete experience of the war, of the indignities of life in the trenched and the dominance of technology, contrasted in significant ways with war as constructed in Seeger’s medievalist imagination. Seeger, however, reconciled this contradiction by seeing the war as part of the elemental Strife of nature. By this means, Seeger avoided the potentially unsettling consequences of confronting the profoundly modern nature of the war. Interpreting the war as a form of “Strife” and as an assertion of medieval values allowed Seeger to imagine himself and his comrades to be living outside the world of industrial capitalist modernity. Seeger shared with others involved in the war this medievalism and the belief that the war offered relief from the values of modernity, even if Seeger’s medievalism was more intense, more thoroughgoing, than was common. However, Seeger’s death as a result of wounds received from machine gun fire vividly displays the contradiction between his imagination and the reality of industrialized warfare. The example of Seeger thus suggests that the American effort in the First World War was underwritten in part by an ideology through which a modern, industrialized war was embraced in terms derived from the imagined medieval past. Insofar as this is true medievalism functioned to provide an ideology that constructed, in the terminology of Raymond Williams, an alternative to the industrial capitalist modernity from which the war emerged, an alternative ideology that allowed the war to be imagined differently from what it was, but which posed no substantive challenge to the war’s social and economic realities.
Keywords: War poetry; Alan Seeger; Medievalism; Ideology; Modernity